Husband Support and The Role of Health Officers with Triple Elimination Examination in Pregnant Women - Siti Rohani; Yuliani Fitria; Rini Wahyuni; Hamid Mukhlis (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Triple elimination examination is carried out for reducing the number of new infections in newborns so that there is a break in the chain of disease transmission from mother to baby. The support from health officers in the form of informational support on how to transmit HIV and its prevention, as well as providing motivation to the community to carry out HIV testing voluntarily. The research objective was to determine the correlation between husband's support and the role of health workers with triple elimination examinations for pregnant women. This research is a quantitative type by uses a cross-sectional analytic approach. The research subjects were pregnant women in the second and third trimesters with the object of this research being the husband's support and the role of health officers. The research was carried out at the Sukarame Public Health Center, Bandar Lampung City in December 2021. The data were collected by using a questionnaire, the data analysis was univariate and bivariate. The results showed that from 146 respondents, 67 respondents (45.9%) carried out the examination, respondents with positive husband support were 75 (51.4%), and respondents with positive health workers were 88 (60.3%). There is a correlation between the husband's support (p-value = 0.003), and there is a correlation between the support of the role of officers (p-value = 0.000) with triple elimination examinations at the Sukarame Health Center in 2021. It is hoped that health workers can provide counseling to pregnant women about the importance of triple elimination examinations through the media leaflets or the internet during visiting Integrated Healthcare Center, and classes for pregnant women. Abstrak: Pemeriksaan triple eliminasi dilakukan untuk menurunkan angka infeksi baru pada bayi baru lahir sehingga terjadi pemutusan mata rantai penularan penyakit dari ibu ke bayi. Dukungan tenaga kesehatan dalam bentuk dukungan informasi baik berupa informasi tentang cara penularan HIV dan pencegahannya, serta memberikan motivasi kepada masyarakat guna melakukan pemeriksaan HIV secara sukarela. Tujuan penelitian untuk mengetahui hubungan dukungan suami dan peran petugas kesehatan dengan pemeriksaan triple eliminasi pada ibu hamil. Penelitian ini jenis kuantitatif menggunakan pendekatan analitik cross sectional. Subjek penelitian adalah ibu hamil pada trimester II dan III dengan objek penelitian ini adalah dukungan suami dan peran petugas kesehatan. Penelitian dilaksanakan di puskesmas Sukarame kota Bandar Lampung pada bulan Desember 2021. Data dikumpulkan dengan menggunakan kuesioner, analisis data secara univariat dan bivariat. Hasil penelitian diketahui dari 146 responden dengan melakukan pemeriksaan sebanyak 67 (45,9%), responden dengan dukungan suami positif sebanyak 75 (51,4%), responden dengan petugas kesehatan positif sebanyak 88 (60,3%). Ada hubungan dukungan suami (p-value = 0,003), dan Ada hubungan dukungan peran petugas (p value = 0,000) dengan pemeriksaan triple eliminasi di Puskesmas Sukarame tahun 2021. Diharapkan petugas kesehatan dapat memberikan penyuluhan kepada ibu hamil tentang pentingnya pemeriksaan tripel eliminasi melalui media leaflet atau internet saat posyandu, dan kelas ibu hamil.